Feeling some typ'a way: A young Black woman's experience of education in South Africa - Shabalala, N. (South African Journal of Higher Education, 2020)
This article aims to contribute to conversations about Black subjectivity by engaging with the reflections of a young, Black, female student at Stellenbosch University. An auto-ethnographic approach is used to demonstrate the complexity of inhabiting multiple intersecting identities. I also explore the internal battles that I have faced and how I constantly negotiate my Blackness. The narrative shows a journey through education while highlighting socio-economic and emotional factors that may contribute to how education is experienced in South Africa.